2008
DOI: 10.1002/jnr.21860
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the 5‐HT3 receptor for days causes sustained relief from mechanical allodynia following spinal cord injury

Abstract: Chronic neuropathic pain is a frequent, serious outcome of spinal cord injury (SCI) that is highly refractory to treatment. Serotonin can contribute to neuropathic pain after SCI, as suggested by our previous observation that transient blockade of the 5-HT(3) receptor by intrathecal injections of the antagonist ondansetron reduces mechanical allodynia after SCI in rats. The current study determined whether intrathecal or intravenous infusion of ondansetron for 3 or 7 days, respectively, could cause sustained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
(51 reference statements)
1
25
0
Order By: Relevance
“…In contrast to the capacity of i.t. injection of ondansetron to attenuate neuropathic pain caused by spinal cord compression [64], this treatment was inactive in SCT rats, probably because complete transection of the spinal cord had suppressed the bulbo-spinal connections involved in 5-HT 3 receptor-mediated effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the capacity of i.t. injection of ondansetron to attenuate neuropathic pain caused by spinal cord compression [64], this treatment was inactive in SCT rats, probably because complete transection of the spinal cord had suppressed the bulbo-spinal connections involved in 5-HT 3 receptor-mediated effects [38].…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal ondansetron attenuated mechanical hyperalgesia and allodynia[34] and inhibited mechanical and thermal evoked responses of spinal dorsal horn neurons in this same model. Spinal administration of ondansetron was also analgesic in models of spinal cord injury, cancer-induced bone pain and osteoarthritis[35-37]. Consistent with reports of pro-nociceptive effects of peripheral 5-HT 3 receptors[38,39], inflammatory pain also appears to be mediated, in part, by spinal 5-HT 3 receptors.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have shown that stimulation of spinal 5-HT 1A (Colpaert et al, 2004;Aira et al, 2010) and 5-HT 1B/1D (Kayser et al, 2002(Kayser et al, , 2011 receptors produces antiallodynic effects, whereas activation of spinal 5-HT 2 (Aira (Rahman et al, 2006;Chen et al, 2009;Wei et al, 2010;Marshall et al, 2012), 5-HT 4 and 5-HT 6 (Rocha-González, personal communication) and 5-HT 7 (Amaya-Castellanos et al, 2011) receptors instead elicits pronociceptive effects. Nevertheless, to the best of our knowledge, no study has investigated directly the role of spinal 5-HT 5A receptors in neuropathic pain models in rats.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, lesions to descending serotonergic projections, by 5,7-dihydroxytryptamine or RNAi for tryptophan hydroxylase-2, reduce 5-HT tissue content and mechanical allodynia in rats with spinal nerve injury (Rahman et al, 2006;Wei et al, 2010;Leong et al, 2011). There is evidence that activation of spinal 5-HT 2 (Aira et al, 2010;Rahman et al, 2011), 5-HT 3 (Rahman et al, 2006;Chen et al, 2009;Wei et al, 2010;Marshall et al, 2012), 5-HT 4 , 5-HT 6 (Rocha-González, personal communication) and 5-HT 7 (Amaya-Castellanos et al, 2011) receptors has been associated with a descending facilitatory role of 5-HT in neuropathic pain models. In contrast, the descending inhibitory role of 5-HT in neuropathic pain models has not been systematically studied.…”
Section: Discussionmentioning
confidence: 96%